Storage fungi and their influence on rice seed quality - H.S. PRAKASH; H. SHEKAR SHETIY, S.P. PURUSHOTHAM, KESHAV L. PATKAR (Indian Phytopathology, 2002)
Rice cv. Rasi seeds were inoculated with spores and treated with culture filtrates of Aspergillus flavus, A. glaucus, A. niger, A. versicolor and Penicillium sp. Seed deterioration was studied based on germination, root and shoot length, total carbohydrate content and alpha-amylase activity. The surface sterilised seeds were inoculated with the spore suspension and incubated at 28+-2degC for up to 30 d. Carbohydrate content and alpha-amylase activity were measured. A. flavus inhibited seed germination and seedling growth the most followed by A. glaucus and A. versicolor. The fungi caused a significant decrease in the total carbohydrate content of seeds. Max. reduction in carbohydrate content was observed in A. flavus inoculated seeds followed by A. versicolor and A. glaucus.